"Everything is telling you to drink": understanding the functional significance of alcogenic environments for young adult drinkers. (2nd November 2018) - Hill, Kimberley M.; Foxcroft, David R.; Pilling, Michael
Abstract: Background: Dominant approaches to understanding alcohol consumption and preventing misuse focus on cognitive antecedents of drinking behaviour. However, these approaches are not only limited, but ignore wider contextual factors. Adopting an ecological approach, this paper considers the functional significance of alcogenic environments from the perspectives of individual drinkers, based on the availability of alcohol-related affordances. Method: Twelve undergraduate students aged 18-30, with a range of self-reported drinking behaviours virtually navigated a range of drinking environments during photo-elicitation interviews. Participants individually described drinking contexts in terms of the form and function-based characteristics that they believed promoted and/or inhibited their alcohol consumption. Results: Interpretative phenomenological analysis revealed the meaning drinking environments had for drinkers, based on their experiences. For participants, alcohol consumption was related to accessibility, communicating with others, consuming food, grasping items, furniture availability, watching or listening to entertainment, advertisement placement, premise décor and alternative action opportunities. Conclusions: Focusing on the functional significance of drinking contexts may be more conducive to understanding contextual factors which may promote or prohibit alcohol consumption. The extent that alcohol-related affordances are linked with excessive consumption and alcohol-related problems merits further study.